2011
DOI: 10.7899/1042-5055-25.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Learning and Study Strategies Inventory Scores Between Chiropractic Students With Lower and Higher Grade Point Averages*

Abstract: Purpose: This pilot study was designed to investigate the relationship between chiropractic students' learning and study strategies and academic performance. Differences in strategic learning between chiropractic students with higher grade points averages (GPAs) and those with lower GPAs have not been previously reported. Methods: Fifty-seven consenting first-trimester chiropractic students self-administered the Learning and Study Strategies Inventory (LASSI). Differences between high and low GPA groups were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 10 publications
4
33
0
4
Order By: Relevance
“…Indeed, there were statistically signifi cant diff erences between higher and lower achieving students in their learning and study strategies. For the participants in this study, scale scores for Anxiety, Attitude, Motivation, Concentration, Selecting Main Ideas, and Test Strategies were signifi cantly higher for the higher group students, which agrees with the study of chiropractic college students ( Schutz, et al ., 2011 ). Prevatt, Petscher, Proctor, Hurst, and Adams (2006 ) compared students with low and high GPAs to identify study skills diffi culties.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, there were statistically signifi cant diff erences between higher and lower achieving students in their learning and study strategies. For the participants in this study, scale scores for Anxiety, Attitude, Motivation, Concentration, Selecting Main Ideas, and Test Strategies were signifi cantly higher for the higher group students, which agrees with the study of chiropractic college students ( Schutz, et al ., 2011 ). Prevatt, Petscher, Proctor, Hurst, and Adams (2006 ) compared students with low and high GPAs to identify study skills diffi culties.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have investigated the relationship between LASSI scale scores and academic performance in healthcare graduate students. This research by Schutz, Gallagher, and Tepe (2011 ) divided a sample of chiropractic students into high and low GPA groups and found that the high GPA group scored signifi cantly higher on LASSI scales of Anxiety, Attitude, Concentration, Motivation, Test Strategies, and Selecting Main Ideas. Sleight and Mavis (2006 ) divided second-year medical students into low, medium, and high cohorts based on Medical College Admission Test (MCAT) scores.…”
mentioning
confidence: 99%
“…Entry GPA was not the major determinant of a student's academic success as noted in other studies. [2][3][4][5] Such consistent trends evident in most institutions of higher learning tend to point to each enrolling institution to cultivate enrolled students into competent and polished doctors at the end of the curriculum to meet the demanding needs of the public. The majority of participants in our study had been encouraged to keep up with their studies right from the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…More current research in chiropractic and other health fields support the view that a high pre-accumulative GPA is a good predictor of one's academic success. [2][3][4][5] Whereas some studies show that students with a higher entry GPA tend to perform better, others show the contrary. Abedi studied the correlation between graduate academic success and undergraduate academic performance and concluded that undergraduate GPA did not have any relationship with graduate academic success.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Although we found no systematic studies relating anxiety and test performance in chiropractic students, the existence of substantial anxiety in chiropractic students is widely recognized. 21,22 To our knowledge, this is the first systematic study to examine test anxiety and performance in chiropractic students.…”
Section: Spielberger and Sarasonmentioning
confidence: 99%